The ecology, vegetation and land use of subhumid Nigeria - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1986)
Describes the geology, relief, climate, major soil types, vegetation zones and land use patterns of the subhumid zone of Nigeria. Presents results of studies on natural forage productivity & composition and forage production constraints.